Dynamic analysis of sectoral linkages for resilient development in Xizang based on input-output model - Hu, Yaokun; Liang, Qiaoxia; Zhang, Wei (Frontiers in Environmental Science, 2025)
IntroductionThe Tibetan Plateau, regarded as China's “national ecological security barrier,” faces challenges in balancing resilient economic growth and environmental protection under climate change.MethodsThis study applies an input-output (IO) model combined with a four-quadrant resilience framework to analyze the linkages and ripple effects of 21 sectors in the Xizang Autonomous Region during 2012-2017.ResultsThe results show that the overall intermediate input coefficient rose from 2012 to 2017, reflecting industrialization but with evident sectoral disparities. Specifically, the primary industry remains underdeveloped, whereas the secondary industry and traditional services are resource-intensive and technologically weak, failing to transition into modern industries characterized by low resource use and high value added. Recent policy adjustments have reduced the influence of high-energy-consuming sectors; however, weak integration with local resources has limited the economic spillover effects of distinctive local assets. Structurally, most sectors exhibit path dependence shaped by existing structures and comparative advantages. Notably, only three sectors (materials; accommodation and catering; wholesale and retail) shifted categories over the past decade, reflecting growing economic reliance on raw materials and tourism and signaling rising environmental pressures.DiscussionThe findings indicate that environmental protection will become increasingly vital for enhancing economic resilience in Xizang. Accordingly, the study calls for sector-specific pathways of industrial upgrading, technological innovation, and supportive policy interventions to foster resilient economic growth while maintaining ecological security.